EFFECT OF pH ON LIQUID-PHASE MASS TRANSFER AND DIFFUSIVITY COEFFICIENT AT LEACHATE TREATMENT OF MUNICIPAL WASTE LANDFILL IN ANAEROBIC BIOREACTOR - Abdul Kahar; IDAA Warmadewanthi; Joni Hermana (Eksergi, 2018)
Leachate is a liquid waste resulted from physical, biological and chemical decomposition of landfill waste. Leachate contains complex dissolved organic and anorganic substrate which are biodegradable and non-biodegradable. Anaerobic treatment principally utilizes anaerobic bacteria in order to degrade the dissolved organic substance into biogas. Anaerobic treatment is very sensitive towards the substrate cocentration, temperature, and pH. This research used anaerobic bioreactor with the volume of 160 L, the ratio of the leachate: biogas is 70:30. Seeding and acclimatization steps were done, respectively for 10 days, leachate treatment was done in 21 days. Seeding, acclimatization, and leachate treatment were done on the pH ambience of 7.2 and 8.0 and ambient temperature. COD and VFA analysis were done every two days. The objective of this research is to decide the pH effect on the coefficient of liquid-phase mass transfer: kL, and the diffusivity of the dissolved substace, DL. pH affects the degradation of the concentratio of dissolved organic substrate in the leachate. The higher the pH is, the higher the obtained VFA concentration is. VFA concentration is affected by pH; however, it still considers the optimal pH condition of the substrate biodegradation. pH affects the average rate of mass transfer, rkL and diffusivity of the dissolved substance, DL in the anaerobic treatment of leachate. pH affect the concentration of dissolved organic substrate which subsequently influenes the coefficient of liquid-phase mass transfer of the leachate, kL and the diffusivity of the dissolved substance, DL. The higher the pH is, the more increasing the kL is and the more decreasing the DL is.